Serviço Social e trabalho docente: precarização e intensificação do trabalho nas Instituições Privadas de Ensino Superior em São Paulo - Albuquerque, Valéria de Oliveira (2015)
This thesis discusses the teaching in higher education Private institutions in the city of São Paulo (IPES), and aims to analyze the conditions and relations in which this work is done, individualising its implementation, especially in the context of growth private education. With regard to the object of this study, we consider teaching a type of work inserted in capitalist relations of production and their living subjects - teachers - employed in the service sector. We tried to understand how higher education facing the market and the capitalist sociability conditions, determines and features the work of social worker in teaching, and to identify current strategies of labor precarization ties and intensification of the teaching workload social worker in IPES. For the unveiling of the thesis subject, bibliographical and documentary research has been done, and access to other sources as major newspapers and internet research, considering the rapid changes in the nature of the sponsors of the IPES, in these last five years have engaged in intense economic processes of sale, merger, acquisition and opening of capital in the stock market, which imposed new elements for teaching and research. To collect empirical data, there was qualitative research, based on semi-structured interviews and form, and personal contacts, by email or by phone. Direct observation was due to some interviews have taken place in the space of IPES, where interviewed on assignment. The research sample comprised 14 Private Institutions of Higher Education (IPES), offering classroom course of social work in the city of São Paulo. The subject of research were 13 social workers teachers, with bond of at least 3 semesters in a row in the same IPES. The analysis, based on the studies and the results of empirical research, pointed out that the main factor of precarization and intensification of teaching is the incompatibility between the procurement regime hourly and own demands of teaching in university teaching